Financial Toxicity and Its Associated Factors in Cancer Patients: A Cross-sectional Study in Indonesia - Handayani, Dewi; Afiyanti, Yati (Nurse Media Journal of Nursing, 2023)
Background: Financial toxicity has been shown to negatively affect cancer patients’ quality of life, depression, anxiety, and even mortality rates. However, there is only limited data on financial toxicity and its associated factors, which are needed to address this problem in Indonesia. Purpose: This study aimed to identify factors associated with financial toxicity in cancer patients in Indonesia.Methods: This study was a cross-sectional study that recruited respondents at a cancer health center in Indonesia using a convenience sampling method. A total of 110 adult cancer patients undergoing treatment took part in the study. The questionnaires comprised sociodemographic data, clinical characteristics, and the Comprehensive Score for Financial Toxicity (COST). Logistic regression was performed to achieve the study's aim.Results: The median value of the financial toxicity index was 3.01 (min-max=1-5), indicating a medium level of financial toxicity. Occupational status was the only factor found to be associated with financial toxicity in this study. The participants who were unemployed were 2.389 more likely to have a higher financial toxicity level compared to those who were employed (OR=2.389; p=0.048).Conclusion: Unemployment was identified to be associated with financial toxicity among cancer patients. Nurses should assess and assist patients in utilizing financial resources and develop strategies to manage extra costs that burden them financially. Future nationwide studies are essential to provide more robust evidence on multifaceted factors influencing financial toxicity and inform policy-making aimed at effectively addressing financial toxicity.